Persistent cryoglobulinemia after antiviral treatment is associated with advanced fibrosis in chronic hepatitis C patients. - Batbold Batsaikhan; Ching-I Huang; Ming-Lun Yeh; Chung-Feng Huang; Yi-Hung Lin; Po-Cheng Liang; Ming-Yen Hsieh; Yi-Ching Lin; Jee-Fu Huang; Wan-Long Chuang; Jin-Ching Lee; Ming-Lung Yu; et al. (PLoS ONE, 2022)
Background High dosage and longer duration of antiviral treatment has been suggested to treat cryoglobulinemia patients. We aimed to investigate the efficacy of antiviral treatment in cryoglobulinemia patients and analyze the associated factors of persistent cryoglobulinemia. Methods Totally 148 patients after completion of anti-HCV treatment were enrolled in our study. Serum cryoglobulinemia precipitation was assessed and analyzed for the associated factors after antiviral therapy. Results Fifty-one (34.5%) out of 148 patients were positive for serum cryoglobulinemia after completion of antiviral therapy. In multivariate analysis, advanced fibrosis (Odds Ratio [OR]- 4.13, 95% Confidence Interval [95% CI]- 1.53-11.17, p = 0.005) and platelet counts (OR-0.98, 95% CI- 0.97-0.99, p = 0.010) were independently and significantly associated with persistent cryoglobulinemia. The factors associated with the persistent cryoglobulinemia in SVR patients were advanced fibrosis (OR-1.93, 95% CI- 1.02-3.65, p = 0.041) and platelet count (OR-0.98, 95% CI- 0.96-0.99, p = 0.041) by multivariate analysis. Multivariate logistic regression analysis showed persistent (OR-4.83, 95% CI- 1.75-13.36, p = 0.002) was significantly associated with advanced fibrosis in patients with cryoglobulinemia follow up after antiviral therapy. Conclusions The prevalence of the persistent cryoglobulinemia is 34.5% after completing antiviral therapy and it is associated with advanced fibrosis, also HCV clearance.